Analysis of waiting time for prescription services at the outpatient pharmacy installation of hospital x Pariaman city - Yonrizon Yonrizon; Renatalia Fika; Adek Septiani Ratna Sari (Institute of Computer Science (IOCS), 2023)
This study aims to determine the average waiting time for prescription services in the outpatient pharmacy installation of Hospital X Pariaman City. The waiting time for finished medicine (non-recipe) is the time from the patient submitting the prescription to receiving the finished medicine (non-recipe) with a minimum standard set ≤ 30 minutes. While the waiting time for concoction drug services is the time from the patient submitting the prescription to receiving concoction drugs with a minimum standard set ≤ 60 minutes. The method used in this study was incidental sampling technique. The number of samples in this study were 379 prescriptions. The average waiting time obtained for non-recipe recipes was 55.92 minutes and concoctions 61.23 minutes. The average waiting time obtained from this study has not met the Minimum Service Standards (MSS) set by the government in the Decree of the Minister of Health (Kepmenkes) of the Republic of Indonesia Number: 129/Menkes/SKII/2008. Factors that influence the length of waiting time for prescription services are officer shifts and the availability of Hospital Human Resources (HR).